Estudo eletroquímico do azul de metileno adsorvido sobre sílica gel quimicamente modificada com óxido de nióbio - Schiavo,Débora de Almeida (2000)
Methylene blue (AM) was immobilised on surface of the silica gel modified with niobium oxide. This material was incorporated in a carbon paste electrode, which showed a redox couple in a potential of E= -113 mV vs SCE in KCl solution at pH 7.0. The formal potential, in 0.5 mol L-1 KCl at pH 7.0, shifted about 290 mV towards more positive values compared to those observed for AM solubilized in aqueous solution. The dependence on the formal potential with solution pH between 2 and 7 was much lower than those observed for AM solubilized in aqueous solution.